2017
DOI: 10.24961/j.tek.ind.pert.2017.27.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Sintesis Surfaktan Alkil Poliglikosida (Apg) Berbasis Dodekanol Dan Heksadekanol Dengan Reaktan Glukosa Cair 75%

Abstract: Alkyl poliglucosides (APG) is nonionic surfactant prepared from renewable raw materials based on carbohydrate and vegetable oils namely glucose and fatty alcohol. Glucose is the main raw material which is ABSTRAKAlkil poliglikosida (APG) merupakan surfaktan non ionik yang dihasilkan dari bahan baku yang dapat diperbaharui berbasis karbohidrat dan minyak nabati yaitu glukosa dan alkohol lemak. Glukosa merupakan bahan baku utama yang membentuk gugus hidrofilik dan alkohol lemak membentuk gugus hidrofobik. Surfak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
0
0
1
Order By: Relevance
“…Density is an essential parameter for surfactants due to the relevance in the application. Generally, surfactants require a density value with a small difference compared to solvent or product, to facilitate mixing and maintain the stability of emulsion (Uzwatania et al, 2017). In this research, FAME has a density of 0.876±0.002 g/cm 3 , consistent with a study of Ghazanfari et al (2017), which reported that the density of FAME from palm oil ranges from 0.843 to 0.890 g/cm 3 .…”
Section: Densitysupporting
confidence: 86%
“…Density is an essential parameter for surfactants due to the relevance in the application. Generally, surfactants require a density value with a small difference compared to solvent or product, to facilitate mixing and maintain the stability of emulsion (Uzwatania et al, 2017). In this research, FAME has a density of 0.876±0.002 g/cm 3 , consistent with a study of Ghazanfari et al (2017), which reported that the density of FAME from palm oil ranges from 0.843 to 0.890 g/cm 3 .…”
Section: Densitysupporting
confidence: 86%
“…Foam stability is achieved through the presence of foaming agents (surfactants). These foaming agents are adsorbed at the interface between phases and trap gas bubbles, resulting in stability [14]. The highest foam stability value was 83.53% obtained by sample F5 with a kaolin concentration of 25% and a sucrose laurate ester concentration of 4%.…”
Section: Resultsmentioning
confidence: 99%
“…Surface tension is a force that arises due to the contact between two different-phase liquids [14]. Surface tension causes the liquid to minimize its surface area.…”
Section: Surface Tension Figure 4 Effect Of Kaolin and Sucrose Ester ...mentioning
confidence: 99%
“…pH sangat penting dalam proses pemilihan GE terbaik, karena pH yang terlalu asam dapat merusak mesin dan dapat menyebabkan korosi. Sebaiknya pH surfaktan yang dipilih adalah 7-9 (Uzwatania et al, 2017).…”
Section: Sintesis Gliserol Esterunclassified